Screening of Vip Gene in Bacillus thuringiensis Isolated from Different Geographical Areas of Nepal and Vip Protein Effect on Fall Armyworm - Upadhyaya, Elisha; Siddiqui, Mohammad Ataullah; Regmi, Sunil; Poudel, Ram Chandra; Khadka, Deegendra; Rana, Nisha; Maharjan, Jyoti; Sijapati, Jaishree (Journal of Nepal Biotechnology Association, 2026)
Incautious use of chemical pesticides in the agricultural field has led to detriment of lands and decline soil fertility. It also poses human health risk and environmental degradation. Bacillus thuringiensis, a spore forming soil bacterium, predominantly produces insecticidal proteins, is a promising solution for sustainable pest management in agriculture. The present work aims to screen Vip genes in isolated stock samples of B. thuringiensis and to show the insecticidal effect of Vip 3 protein on Fall armyworm larva. Fifty B. thuringiensis isolates along with two commercial strains, B. thuriengiensis subsp. galleriae HD8 (BGSC 4G1) and B. thuriengiensis subsp. morrisoni HD12 (BGSC 4K1), were used for screening of vegetative insecticidal protein coding genes (Vip1, Vip2 and Vip3) by conventional PCR and sequencing. Gram staining was performed for bacterial morphology and only bipyramidal shaped protein crystals were visualized during Coomassie Brilliant Blue staining. Among 50 crystal-forming isolates, 90% strains were found to carry the Vip3 gene but none of the isolates were found to possess the Vip1 and Vip2 genes. However, Vip2 gene was detected in reference strains (BGSC 4G1 and BGSC 4K1). The pairwise comparisons and phylogenetic tree analysis of Vip3 genes from five Bt isolates showed 100% sequence similarities with worldwide distributed B. thuringiensis Vip3 gene. Ammonium sulfate precipitation was followed by partial purification of Vip3 protein. SDS-PAGE analysis revealed the molecular weight of the Vip3 protein around 90 KDa. From bioassay of Fall armyworm, lethal concentration (LC50) of Vip3 protein of reference sample BGSC 4G1 was 16.2607 ± 5.4239 μg/ml and isolate Bt Kasara showed 19.1268 ± 8.289 μg/ml in 7 days. Protein of BGSC 4G1 showed strong effectiveness (needed 17.63% less protein) as compared to Bt Kasara Vip3 protein. Therefore, Vip3 protein showed a potential biopesticidal effect and it may be utilized as a sustainable pest management approach.